Identification of a Novel Alternative Splicing Variant of VvPMA1 in Grape Root under Salinity - Han, Ning; Ji, Xing-Long; Du, Yuan-Peng; He, Xi; Zhao, Xin-Jie; Zhai, Heng (Frontiers in Plant Science, 2017)
It has been well demonstrated that the control of plasma membrane H+-ATPase (PM H+-ATPase) activity is important to plant salt tolerance. This study found a significant increase in PM H+-ATPase (PMA) activity in grape root exposed to NaCl. Furthermore, 7 Vitis vinifera PM H+-ATPase genes (VvPMAs) were identified within the grape genome and the expression response of these VvPMAs in grape root under salinity was analyzed. Two VvPMAs (VvPMA1 and VvPMA3) were expressed more strongly in roots than the other five VvPMAs. Moreover, roots exhibited diverse patterns of gene expression of VvPMA1 and VvPMA3 responses to salt stress. Interestingly, two transcripts of VvPMA1, which were created through alternative splicing (AS), were discovered and isolated from salt stressed root. Comparing the two VvPMA1 cDNA sequences (designated VvPMA1α and VvPMA1β) with the genomic sequence revealed that the second intron was retained in the VvPMA1β cDNA. This intron retention was predicted to generate a novel VvPMA1 through N-terminal truncation because of a 5’- terminal frame shift. Yeast complementation assays of the two splice variants showed that VvPMA1β could enhance the ability to complement Saccharomyces cerevisiae deficient in PM H+-ATPase activity. In addition, the expression profiles of VvPMA1α and VvPMA1β differed under salinity. Our data suggests that through AS, the N-terminal length of VvPMA1 may be regulated to accurately modulate PM H+-ATPase activity of grape root in salt stress.